2014
DOI: 10.3389/fpsyg.2014.00954
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between language proficiency and attentional control in Cantonese-English bilingual children: evidence from Simon, Simon switching, and working memory tasks

Abstract: By administering Simon, Simon switching, and operation-span working memory tasks to Cantonese-English bilingual children who varied in their first-language (L1, Cantonese) and second-language (L2, English) proficiencies, as quantified by standardized vocabulary test performance, the current study examined the effects of L1 and L2 proficiency on attentional control performance. Apart from mean performance, we conducted ex-Gaussian analyses to capture the modal and positive-tail components of participants' react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 65 publications
(130 reference statements)
2
58
0
Order By: Relevance
“…In accord with these findings, Tse & Altarriba (2014) tested a group of Cantonese-English bilingual children and revealed a lack of association between measures of language proficiency and ex-Gaussian parameters in a non-linguistic Simon switching task.…”
Section: Introductionmentioning
confidence: 80%
“…In accord with these findings, Tse & Altarriba (2014) tested a group of Cantonese-English bilingual children and revealed a lack of association between measures of language proficiency and ex-Gaussian parameters in a non-linguistic Simon switching task.…”
Section: Introductionmentioning
confidence: 80%
“…Barac and Bialystok (2012) report bilingual advantages in Canadian schoolchildren who were bilingual in French, Spanish, or Chinese with English relative to monolingual English children recruited from the same schools, but they found no differences in EF performance attributable to culture. Tse and Altarriba (2014) reported that higher levels of L2 English proficiency in L1 Cantonese speakers in Hong Kong was related to a smaller Simon Effect, and Yang et al (2011) found both an advantage of Korean culture and bilingualism in children, suggesting dissociable benefits of both. However, it is true that there is also a great deal of evidence suggesting an absence of a bilingual advantage in within-culture studies.…”
Section: Discussionmentioning
confidence: 99%
“…For our review, we first selected those studies found in recent meta‐analyses and reviews (Donnelly et al., ; Hilchey & Klein, ; Lehtonen et al., ; Paap et al., ; Sanchez‐Azanza, López‐Penadés, Buil‐Legaz, Aguilar‐Mediavilla, & Adrover‐Roig, ; Zhou & Krott, ). We included only studies that (a) are published (excluding for example, doctoral theses); (b) include one or more of the Simon Task, Flanker task (as part of the ANT or separately), or Spatial Stroop task; (c) include a healthy monolingual as well as a healthy bilingual group, or at least included a reportedly bilingual sample that incorporated participants who would be classified as monolingual (e.g., Tse & Altarriba, ); (d) measure or define language proficiency in a quantifiable (e.g., numeric) way, or at least descriptively in terms of competence, but not in terms of national‐level exam passes (e.g., Wang, Fan, Liu, & Cai, ); v) are not re‐analyses of data reported in an earlier paper (e.g., Calabria, Hernández, Martin, & Costa, ); and vi) did not adapt the task or stimuli such that it made qualitatively different demands on participants relative to the original design (e.g., the LANT used by Marzecová, Asanowicz, Kriva, & Wodniecka, ), or any instance of linguistic stimuli rather than the standard shapes or symbols (e.g., Rubio‐Fernández & Glucksberg, ). To ensure an up‐to‐date assessment of the literature, we also conducted a search using Web of Science, using the two obligatory search terms “Bilingual” and “Monolingual,” and then adding one at a time each of “Simon,” “Flanker,” Spatial Stroop,” “Arrows,” and “ANT.” We then conducted the same searches once more without the term “Monolingual” to ensure we included tasks where no explicit monolingual group was present but the study included a meaningful amount of data from participants that were closer to the monolingual end of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Bilingual children outperformed their monolingual peers on this task, a finding that has been replicated in other studies (Carlson & Meltzoff, 2008; Esposito, Baker-Ward, & Mueller, 2013). For instance, in a recent study with older bilingual children (5 to 9 year-olds), increased proficiency in a second language was associated with better inhibitory control (Tse & Altarriba, 2014). …”
Section: More Of the Same: Trilingualism Does Not Change The Bilinmentioning
confidence: 99%